ANALISIS EFEKTIVITAS MEDIA CHANNEL DIGITAL DALAM MENDORONG BRAND AWARENESS PT. GOJEK INDONESIA AREA BALI - Familya Maria D.L. Moensaku; Merlyn Kurniawati; Yonas F Riwu; Rolland E. Fanggidae (LPPM STIE Muhammadiah Bandung, 2025)
The study aims to analyze the effectiveness of digital media channels used to increase brand awareness at PT. Gojek Indonesia Area Bali with a digital community based marketing strategy amid increasingly competitive on-demand services. Bali, as an international tourist destination, has heterogeneous consumer characteristics, including local residents and domestic and foreign tourists. Gojek, in the midst of digitalization, leverages social media platforms such as Instagram, TikTok, and YouTube, and utilizes community based content tailored to promotional campaigns that align with the characteristics of local users, culture, and tourists in Bali to build closer relationships and strengthen the brand image among consumers. The research approach uses a sequential exploratory mixed-method combining in depth interviews and participatory observation (qualitative) with a Likert scale survey of active social media users in Bali (quantitative). The effectiveness of digital media channels is then analyzed through three marketing effectiveness indicators by Smith et al. (2023), namely outcome-based (final results in the form of increased brand awareness, new users, and subscription transaction conversions), process-based (content strategy and digital campaign management), and impact-based (engagement rate). The research results indicate that community marketing integrated with digital media and local culture can significantly increase Gojek's brand awareness. User-generated content (UGC) and digital word-of-mouth marketing (eWOM) have proven to expand campaign reach and enhance user emotional engagement. This study contributes to the development of community-based digital marketing strategies in on-demand services and offers practical implications for Gojek to optimize a more personalized, relevant, and contextual digital approach in the Bali region.